Earthquake relocation for North-Western Greece using 3D crustal model; method comparison and seismotectonic interpretation. - Stavroulopoulou, O.; Sokos, E.; Martakis, N.; Tselentis, G. A. (Bulletin of the Geological Society of Greece, 2013)
A dense microseismic network was installed in Northwestern Greece for a period of eleven months. A total of 1368 events were recorded and located using a 1D model. These events were also used to derive a 3D velocity model for the area. This work presents results from further processing of the data using (a) simple location method of events in a 1D medium through Hypo71 standard procedure; (b) location via the probabilistic, non-linear earthquake location method in 3D medium; (c) relocation of the events using the Double - Difference method in 1D medium; and (d) the same relocation procedure invoking 3D medium. The application of different location methodologies results in slightly different locations, which are evaluated using as criterion the compactness of hypocenter distribution. The three point method was used in order to derive linear characteristics from the hypocenter distribution and the final results were compared against the focal mechanisms of the events as computed using the polarity method and the 3D velocity model. The combination of accurately computed hypocenters and focal mechanisms provides important information for the seismotectonics of Epirus